High glucose contributes to the proliferation and migration of non-small-cell lung cancer cells via GAS5-TRIB3 axis. Issue 2 (16th March 2018) - Ding, Cheng-Zhi; Guo, Xu-Feng; Wang, Guo-Lei; Wang, Hong-Tao; Xu, Guang-Hui; Liu, Yuan-Yuan; Wu, Zhen-Jiang; Chen, Yu-Hang; Wang, Jiao; Wang, Wen-Guang
Abstract : Despite the growing number of studies exhibiting an association of diabetes mellitus (DM) and lung cancer progression, the concrete mechanism of DM aggravating lung cancer has not been elucidated. The present study was to investigate whether and how high glucose (HG) contributes to the proliferation and migration of non-small-cell lung cancer (NSCLC) cells in vitro . In the present study, we confirmed that HG promoted the proliferation and migration of NSCLC cells, and also induced an anti-apoptotic effect on NSCLC cells. Moreover, HG inhibited the expression of growth arrest-specific 5 (GAS5) in NSCLC cells but elevated the protein level of tribbles homolog 3 (TRIB3). GAS5 overexpression promoted the degradation of TRIB3 protein by ubiquitination and inhibited the HG-induced proliferation, anti-apoptosis, and migration of NSCLC cells. Importantly, TRIB3 overexpression reversed the effects of GAS5 on the HG-treated NSCLC cells. Taken together, down-regulated GAS5 by HG significantly enhanced the proliferation, anti-apoptosis, and migration in NSCLC cells through TRIB3, thus promoting the carcinogenesis of NSCLC.